2012
DOI: 10.1021/ac300578n
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Labeling and Isotope Dilution Analysis for the Quantification of the Peptide Hepcidin-25 in Serum Samples by HPLC-ICP-MS

Abstract: Hepcidin-25 is a peptide-hormone that has been proposed as the key biomarker for the diagnosis and monitoring of iron disorders. Structurally, hepcidin-25 is a S-rich peptide (with 8 cysteines and 1 methionine) that contains a metal binding motif in the N-terminus. That domain binds preferably Cu(II) ion forming a stable complex. Such selective binding can be used as mean to determine hepcidin-25 in biological fluids by highly sensitive Cu measurement. Thus, we use liquid chromatography coupled to inductively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The fragmentation of the triply charged quasi-molecular ion as the most intense precursor ion resulted in the same fragment y22 2+ (1218.2 Da) compared to the fragmentation pattern of hepcidin-25, and a fragment of 415 Da which corresponds to a copper-adduct of the N-terminal fragment containing the three amino acids of the ATCUN motif (Asp-Thr-His). The difference of 61 Da corresponds indeed to the addition of one copper (62.9 Da) and the loss of 2 Da and 2 positive charges (2 H + ), in accordance with previous findings [28,33]. Analyzing the solution of hepcidin-Cu 2+ (molar ratio 1:10) revealed a hepcidin-25 species complexed with two Cu 2+ -ions.…”
Section: Ms/ms Characterization Of Hepcidin-25 and Hepcidin-25-coppersupporting
confidence: 91%
See 3 more Smart Citations
“…The fragmentation of the triply charged quasi-molecular ion as the most intense precursor ion resulted in the same fragment y22 2+ (1218.2 Da) compared to the fragmentation pattern of hepcidin-25, and a fragment of 415 Da which corresponds to a copper-adduct of the N-terminal fragment containing the three amino acids of the ATCUN motif (Asp-Thr-His). The difference of 61 Da corresponds indeed to the addition of one copper (62.9 Da) and the loss of 2 Da and 2 positive charges (2 H + ), in accordance with previous findings [28,33]. Analyzing the solution of hepcidin-Cu 2+ (molar ratio 1:10) revealed a hepcidin-25 species complexed with two Cu 2+ -ions.…”
Section: Ms/ms Characterization Of Hepcidin-25 and Hepcidin-25-coppersupporting
confidence: 91%
“…Some authors applied FTICR-MS measurements at pH of 6.8 and found total complex formation at molar ratio hepcidin-25:copper of 1:1 [28], while other authors reported the presence of unreacted peptide at equimolar concentrations, in a q-ToF-MS (Quadrupol-Time-of-flight mass spectrometry) experiment at pH of 8.2. [33]. Fig.…”
Section: Molecular Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates the stability of the copper-binding motif that is preserved even during MS fragmentation. Furthermore, the affinity of hepcidin-25 for copper allowed the quantification of the peptide in serum samples using inductively coupled plasma mass spectrometry (ICP-MS) by employing direct biomolecule labeling [29]. Publications regarding N-terminus of Hep-25 reported this motif to be unstructured in contrast to the rest of the molecule which is highly rigid due to four intramolecular disulfide bridges [5,6].…”
Section: Introductionmentioning
confidence: 99%